Avaliação física, química e sensorial de genótipos de uvas com potencial para produção de passas no submédio do vale do São Francisco - Viera, Danise Medeiros (2016)
The Lower Basin of the São Francisco Valley is an important region for production of fine table grapes, representing more than 95% of the national grape exports. However, grapes outside the standard for export are sold at discounted prices and are often intended for discart. The objective of this study was to evaluate the potential of grapes produced in the Lower Basin of the São Francisco Valley for the production of raisins. Six grape genotypes without seeds were used in our study: four tint (Cnpuv 8, Adona, BRS Victory BRS Isis) and two white (A1105 and Thomson Seedless). After, grapes were destemmed, sanitized, treated with 1mol.L-1 NaOH and dried at 60 °C. Later, raisins were physically and chemically characterized. The treatment with 1% NaOH was efficient to trigger skin rupture, increasing water loss and reducing drying time. For maintaining the color of the white grapes (A1105), raisins without the use of antioxidants had a lighter color, next to the fruit when in nature. ‘Thompson Seedless’ raisins had higher soluble solids with 43.78 ° Brix and ‘Adona’ had higher titratable acidity, 3.00% tartaric acid, whereas ‘BRS Isis’ had the highest firmness, 90,12g. The genotype had a strong effect on raisin sensory profile. ‘Adona’ and ‘Cnpuv8’ showed higher intensity of caramelized flavor, sweet taste, dry fruit flavor and firmness. ‘BRS Victoria’ raisins had greater acceptance averaging 6.8 in hedonic scale of 9 points and purchase intention to purchase 65% of consumers. ‘Thompson Seedless’ raisins genotype had the highest concentration of sugar, 736.05 g kg-1, while ‘BRS Isis’ and ‘BRS Victoria’ had the highest concentrations of total phenolics and anthocyanins. All red cultivars showed higher concentrations of stilbene, flavonols, flavanols and total phenolic acids higher than ‘Thompson Seedless’. The highest concentration of flavonols was observed ‘BRS Isis’ with 181 mg Kg-1. ‘BRS Victoria’ had the highest concentrations of phenolic acids and stilbene trans-resveratrol at 31.87 and 4.37 mg Kg-1 of dried weight, respectively.